Interactive effects of dispositional mindfulness and PETTLEP imagery training on basketball shooting performance: A randomized controlled trial. (March 2023) - Fang, Bin-Bin; Lu, Frank J.H.; Gill, Diane L.; Chiu, Yi-Hsiang; Cheng, Yi-Chia; Hsieh, Ming-Hui; Zhang, Zhiyang
Abstract: The purpose of this study was to examine the interactive effects of dispositional mindfulness and visualized PETTLEP imagery training on basketball mid-range shooting performance and retention. Seventy-three participants ( M age = 20.32 ± 1.09) with high/low dispositional mindfulness (high n = 35; low n = 38) selected out of 302 college students were randomly assigned into the following six groups: (a) high mindfulness internal imagery (H-II, n = 13); (b) high mindfulness external imagery (H-EI, n = 11); (c) high mindfulness control (H–CO, n = 11); (d) low mindfulness internal imagery (L-II, n = 13); (e) low mindfulness external imagery (L-EI, n = 12); and (f) low mindfulness control (L-CO, n = 13). Participants engaged in a pretest to measure their basketball shooting performance, then participated in a 6-week (3 times/per-week) intervention, plus a posttest and retention test. A three-way 2 (high/low mindfulness) X 3 (treatments: internal-, external imagery, and control) X 3 (measurement time: pretest, posttest, and retention) mixed ANOVA statistical analysis found dispositional mindfulness interacted with treatments and measurement time. The main effects showed high dispositional mindfulness performed better than low dispositional mindfulness, and internal imagery training performed better than external imagery training on mid-range basketball performance at retention. The 3–way interaction indicated that when using either internal or external imagery, high dispositional mindfulness performed better than low mindfulness on retention but not posttest. For 2-way interaction, high dispositional mindfulness performed better than low dispositional mindfulness on retention but not posttest. Our results extended current knowledge on sport imagery and dispositional mindfulness and gained several theoretical implications for researchers. The limitations, future research directions, and practical implications were also discussed. Highlights: When using either internal or external imagery training, high dispositional mindfulness maintained better performance at retention than low dispositional mindfulness. An internal imagery training was superior than external imagery training on basketball mid-range shooting performance in retention. Effects of imagery training on basketball mid-range shooting performance were moderated by participants' dispositional mindfulness.